The relative involvement of Th1 and Th2 associated immune responses in the expulsion of a primary infection of Heligmosomoides polygyrus in mice of differing response phenotype - Ben-Smith, A.W.; Lammas, D.A.; Behnke, Jerzy M. (Cambridge University Press, 2003)
T helper cell (Th1 and Th2) associated responses were examined following a primary infection with the gastrointestinal nematode Heligmosomoides polygyrus in five inbred strains of mice with different resistance phenotypes. Levels of (i) mast cell protease, (ii) specific IgE, (iii) nitric oxide and (iv) specific IgG2a, as markers of Th2 and Th1 associated responses, respectively, were determined in sera and intestinal fluids and correlated with worm burdens. The ‘fast’ responder (resistant) strains SWR and SJL produced strong Th2 and Th1 associated responses respectively in a mutually exclusive fashion. The F1 hybrid(SWR £ SJL) F1, showed rapid expulsion of the parasite and expressed both intense Th1 and Th2 responses, suggesting synergism between Th1 and Th2 activity in these mice. The results indicate that both Th2 and Th1 responses operate in mice following a primary infection with H. polygyrus and that each Th response may be involved to a greater or lesser degree within certain strains. Resistance to H. polygyrus was found to correlate only to the intensity of either the gut-associated mastocytosis or nitric oxide production in these strains but not to either specific IgE or IgG2a titres. Chronic infections in the ‘slow’ response phenotype mouse strains CBA and C57BL/10, were associated with both poor Th2 and poor Th1-associated responses attributed to a general parasite-mediated immunosuppression of the host immune response to infection.